2021
DOI: 10.1038/s41525-021-00178-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic profiles of 103,106 individuals in the Taiwan Biobank provide insights into the health and history of Han Chinese

Abstract: Personalized medical care focuses on prediction of disease risk and response to medications. To build the risk models, access to both large-scale genomic resources and human genetic studies is required. The Taiwan Biobank (TWB) has generated high-coverage, whole-genome sequencing data from 1492 individuals and genome-wide SNP data from 103,106 individuals of Han Chinese ancestry using custom SNP arrays. Principal components analysis of the genotyping data showed that the full range of Han Chinese genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
138
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 50 publications
6
138
1
Order By: Relevance
“…27,719 samples were genotyped on the TWBv1 custom array, which was designed based on Thermo Fisher Axiom Genome-Wide CHB Array with customized contents; 83,207 samples were genotyped on the TWBv2 custom array, which was designed by Thermo Fisher Scientific Inc. based on whole-genome sequencing data from 946 TWB samples with customized contents. 10 We divided the samples genotyped on the TWBv2 array into two subsets, with 68,975 samples for loci discovery and 14,232 samples for polygenic risk score (PRS) analysis. We refer to samples genotyped on the TWBv1 array as “discovery batch 1” and the loci discovery samples genotyped on the TWBv2 array as “discovery batch 2” (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,719 samples were genotyped on the TWBv1 custom array, which was designed based on Thermo Fisher Axiom Genome-Wide CHB Array with customized contents; 83,207 samples were genotyped on the TWBv2 custom array, which was designed by Thermo Fisher Scientific Inc. based on whole-genome sequencing data from 946 TWB samples with customized contents. 10 We divided the samples genotyped on the TWBv2 array into two subsets, with 68,975 samples for loci discovery and 14,232 samples for polygenic risk score (PRS) analysis. We refer to samples genotyped on the TWBv1 array as “discovery batch 1” and the loci discovery samples genotyped on the TWBv2 array as “discovery batch 2” (see Figure 1).…”
Section: Methodsmentioning
confidence: 99%
“…The Taiwan Biobank (TWB) is a community-based prospective cohort study of the Taiwanese population with multi-omics genomic data, and longitudinal phenotypic and environmental measures (see https://www.twbiobank.org.tw/new_web_en/ for more information). Genotyping was performed using two different customized genome-wide arrays 10 . A total of 27,719 participants genotyped on the TWBv1 array and 83,207 participants genotyped on the TWBv2 array were included in this study and subsequently went through genotype quality control (QC) and imputation.…”
Section: Mainmentioning
confidence: 99%
“…Our recent genetic survey focused on geographically distinct Hans also identified their differentiated demographic history: Northwest Hans from Gansu harboring more western Eurasian ancestry; Southwest Hans from Sichuan possessing more genetic influence from Tibeto-Burman speakers; Southmost Hans from Hainan having more ancestry related to Tai-Kadai people; Southeast Hans from Fujian possessing more Austronesian-related ancestry; Central Hans from Chongqing, Guizhou, Hubei, and Hunan harboring equal ancestry related to Neolithic YRB millet farmers and southern indigenes, and North Hans in Shaanxi and Shanxi possessing dominant local millet farmer ancestry. Whole-genome sequence data from Taiwan Hans, Singapore and Peranakan Chinese also showed that Hans outside of Mainland China possessed additional genetic admixture from indigenous Austronesian Ami or Malay (28,29). However, the genetic origin and population structure of Northeast Hans from Inner Mongolia, Jilin, Liaoning and Heilongjiang keep uncharacterized.…”
Section: Genetic History Of Northeast Han Chinese Populationsmentioning
confidence: 99%
“…Third, we did not recruit normal control group in the current survey because the study goal was to identify SNPs associated with AoM in migraineurs. Thus, we checked the allele frequency of these AoM-associated SNPs in Taiwan Biobank, a well-known database that collects information of healthy Taiwanese population [ 19 , 46 ]. The results confirmed that these significant variants were not common variants (MAF < 5 %).…”
Section: Discussionmentioning
confidence: 99%
“…DNA quality was measured using a NanoDrop One spectrophotometer (Thermo Fisher Scientific, Waltham, MA, USA). The genomic DNA was then applied to Affymetrix Axiom Genome-Wide TWB 2.0 arrays, which included approximately 752,921 probes for 686,463 SNPs [ 19 ]. The complete list of variants on the TWBv2 array is available at https://www.twbiobank.org.tw/new_web/exp_doc/TWBv2.0_SNPs%E4 %BD%8D%E9 %BB%9E%E7 %9B%B8 %E9 %97 %9 C%E8 %B3 %87 %E8 %A8 %8 A.zip .…”
Section: Methodsmentioning
confidence: 99%